Legal basis for strengthening democratic principles in parliamentary activity - Makhmatkulova Saida Ilkhom qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
The legal basis for strengthening democratic principles in the activities of the Parliament of the Republic of Uzbekistan is analyzed. It is substantiated that the Parliament is the highest representative body ensuring democratic governance as a practical expression of people's sovereignty. The study covers constitutional and regulatory mechanisms, in particular, the principles of freedom of elections, multi-party system, openness, responsibility of deputies and parliamentary control. Based on legal analysis, comparative and systematic approaches, the experience of Uzbekistan is compared with foreign parliamentary practice. As a result, it was determined that further strengthening democratic principles in parliamentary activities will serve to ensure transparency, balance and participation of civil society in state governance.